Dynamic Conditional Correlation of International and Domestic Meat Price Volatility - Mohd Hafizuddin Ramli; Siti Norzailina Mohamad Noor; Ahmad Fauzi Ismail; Nurul Huda Abdul Rashid (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study aims to examine volatility transmission between international and domestic beef and mutton prices in Malaysia and to assess the role of exchange rate and crude oil price shocks in shaping domestic meat price instability. The study uses monthly data from January 2020 to December 2024 covering domestic retail beef and mutton prices, international meat prices from Malaysia’s major trading partners, the Malaysian Ringgit exchange rate, and crude oil prices. Real price series are transformed into monthly log returns. The analysis applies Constant Conditional Correlation and Dynamic Conditional Correlation multivariate GARCH models, with exchange rate and crude oil prices incorporated as exogenous variables in the volatility equations. Stationarity, autocorrelation, and ARCH diagnostic tests are conducted to validate model suitability. The findings reveal stronger interdependence and volatility transmission in beef markets than in mutton markets. International beef price volatility is transmitted to Malaysia’s domestic beef market, while mutton prices show weaker cross-market linkage but high volatility persistence. Crude oil price volatility significantly increases both beef and mutton price volatility through logistics, cold-chain, and distribution-cost channels. Exchange rate volatility significantly affects beef price volatility, but its effect on mutton is weaker and statistically insignificant. This study contributes to agricultural price volatility literature by applying CCC-DCC MGARCH models to imported meat markets in a post-pandemic, geopolitically unstable context. The findings suggest the need to strengthen domestic livestock production, improve market information systems, stabilize import-related macroeconomic risks, and coordinate food price monitoring policies.